TANGGUNG JAWAB BADAN PERTANAHAN NASIONAL DALAM PEMBERIAN HAK GUNA USAHA (SuatuPenelitian di Provinsi Aceh). - Aris Rubianto, Ilyas Ismail, Suhaimi. (Jurnal Ilmu Hukum, 2015)
Abstract: Article 5 of the Government Regulation Number 24, 1997 regarding Land Registration mention that the registration is conducted by the National Land Board (BPN). Article 9 (1) point a of the Government Regulation Number 24, 1997 that becomes an object of land registration one them is Land Cultivation Right (HGU). The Board responsibility in providing the right is happening when the issuance of location permit, the provision process of the right and also the monitoring and evaluation of the right owner. This thesis aims to explain the legal impact on the responsibility of the BPN responsibility implementation that is conducted that is against the law. The research shows that the responsibility of the BPN in providing the land cultivation right has not been done as demanded by law, there is the permit issuance of location by the Head of District/Major without technical land consideration from the Regional/municipality Land Office and it is not maximally conducted. Legal consequences on the right in the process of providing the right one of the requirements is the Decision of location permit is not based on technical consideration of land can be aborted. While the effect on is no enforcement its conduct is not optimal the enforcement and empowerment of unoccupied land by the right holders is potent to the dispute in the future. It is recommended it should develop good relationship between the BPN and the District/Municipality Government and they should campaign the laws. Keywords: National, Land Board, Responsibility, Cultivation Right Abstrak: Pasal 5 Peratutan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah menyebutkan bahwa Pendaftaran tanah diselenggarakan oleh Badan Pertanahan Nasional (BPN). Dalam Pasal 9 ayat (1) huruf a Peraturan Pemerintah Nomor 24 Tahun 1997 yang menjadi objek pendaftaran tanah salah satunya adalah Hak Guna Usaha (HGU). Tanggung jawab BPN dalam pemeberian HGU terjadi saat penerbitan izin lokasi, proses pemberian HGU serta dalam pengawasan dan evaluasi pemegang hak. Penelitian ini bertujuan menjelaskan akibat hukum yang timbul terhadap pelaksanaan tanggung jawab jawab BPN dalam pemberian HGU yang tidak sebagaimana mestinya. Hasil penelitian menunjukan bahwa masih ada penerbitan izin lokasi oleh Bupati/Walikota tanpa didasarkan atas pertimbangan teknis pertanahan dari Kantor Pertanahan Kabapaten/Kota serta dalam pelaksanaan penertiban dan pendayagunaan tanah telantar belum maksimal. Akibat hukum terhadap HGU yang dalam poses pemberian haknya salah satu persaratanya berupa SK Izin lokasi tidak berdasarkan pertimbangan teknis pertanahan adalah dapat dibatalkan. Sedangkan akibat tidak terlaksana secara optimal kegiatan penertiban dan pendayagunaan tanah terlantar maka tanah yang ditelantarkan oleh pemilik HGU berpotensi menimbulkan sengketa dikemudian hari. Disarankan membangun hubungan baik antara BPN dengan Pemerintah Aceh dan mensosialisasikan peraturan perundang-undangan tentang pemberian HGU kepada Pemerintah Aceh. Kata kunci: Tanggung Jawab BPN, Pemberian HGU.